Regulation of free amino acid and polyamine levels during cold acclimation in wheat - Kocsy, Gábor (Acta Biologica Szegediensis, 2011)
The effect of cold acclimation on free amino acids and polyamines was compared at metabolite and transcript level in wheat chromosome 5A substitution lines with different freezing tolerance. Three weeks at 2°C resulted in increased H2O2 content which alteration may affect the metabolism of these compounds. The concentration of most free amino acids gradually increased during the treatment. The expression of the genes encoding enzymes of amino acid metabolism, thus that of pyrroline-5-carboxylate reductase, glutamate synthetase and aspartate transferase had a fast transient increase during the first days of growth at 2°C. The concentration of the polyamines putrescine and spermidine exhibited a great increase in all three genotypes, while spermine and cadaverine levels showed only slight changes. Among the genes related to the polyamine metabolism, the transcript level of those ones encoding arginine and ornithine decarboxylase increased and that of the spermidine synthetase did not change. The observed changes in metabolite and transcript levels were controlled by chromosome 5A in the case of Pro, Glu and putrescine. The present result show that free amino acids and polyamines play an important role in the cold acclimation and their levels are regulated at the transcriptional level.